2018
DOI: 10.1155/2018/7812743
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Theory of Piezoresistive Effects in Hall Plates with Large Contacts

Abstract: Four-terminal transducers can be used to measure the magnetic field via the Hall effect or the mechanical stress via the piezoresistance effect. Both effects are described by an anisotropic conductivity tensor with small offdiagonal elements. This has led other authors to the conclusion that there is some kind of analogy. In both cases the output voltage depends on the geometry of the device and the size of the contacts. For Hall plates this influence is accounted for by the Hall-geometry factor. The alleged a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…Our new theory can be applied to Hall plates with anisotropic conductivity as it is caused by mechanical stress in a cubic crystal. Then, in a preceding isotropization step, one can replace the original geometry by a distorted geometry with isotropic conductivity (see [16] and references therein). This procedure does not change the number of holes in a multiply-connected Hall plate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our new theory can be applied to Hall plates with anisotropic conductivity as it is caused by mechanical stress in a cubic crystal. Then, in a preceding isotropization step, one can replace the original geometry by a distorted geometry with isotropic conductivity (see [16] and references therein). This procedure does not change the number of holes in a multiply-connected Hall plate.…”
Section: Discussionmentioning
confidence: 99%
“…The meaning of (14a) is: Since odd J is a vector field free of sources, its flux through any closed contour C in the multiply-connected Hall plate vanishes, and therefore odd J can be expressed as the curl of a magnetic field In (17a), we were allowed to add odd J in the integrand because integration of odd ⋅ J n over a closed path gives zero according to (16). The circulation of a specific pattern of spiral current streamlines is computed in Appendix A.…”
Section: Hall Plates With Point Current Contacts On Different Boundarmentioning
confidence: 99%
“…After all shear stress diverts the current streamlines and this may well affect 0 H G . In [13] it was shown that shear stress (or in general any in-plane biaxial stress) changes 0 H G for Hall plates unless they have 90° symmetry. In the case of Vertical Hall devices inplane shear stress xy  tilts the current streamlines out of the (x,z) cross-section plane.…”
Section: The Thick Vertical Hall Devicementioning
confidence: 99%
“…Yet a small part may also come from piezo-resistance effect, which diverts the current flow lines thereby changing the Hall geometry factor (cf. section 5 of [13]). Stress is also a major source of offset error (zero point error) of Hall plates and to a lesser extent of Vertical Hall devices [13,13b].…”
mentioning
confidence: 99%
“…We note that anisotropy generated by piezoresistive effects is not analyzed here. This subject was addressed in the excellent paper by Ausserlechner [23].…”
Section: Introductionmentioning
confidence: 99%